Readiness for new ventures in South Africa through entrepreneurship education: a reflective thematic approach - Thobekani Lose; Priviledge Cheteni (Cogent Business & Management, 2024)
The purpose of this research is to investigate what factors affect students' readiness to start their own businesses once they graduate from university. A case study approach was conducted with an emphasis on an undergraduate degree program at a South African university. Data was collected through semi-structured interviews with 15 program participants and analysed using a reflective theme analysis method. Our findings suggest that the experiential learning methodology employed at the university increases students' levels of self-efficacy in the realm of entrepreneurship, i.e. their belief in their own abilities to create and run successful firms. They look at the benefits of going into business for themselves with optimism. However, our findings suggest that certain students may lack the confidence to take initiative to try entrepreneurship.major implication of these findings is that student readiness for entrepreneurship ventures is influenced by a multitude of factors which are beyond training. It is recommended that students participating in entrepreneurship programmes given support after graduation to realise their goals.
Keywords: 650; Entrepreneurship education; innovation in business; training in entrepreneurship; entrepreneurial intentions